2003
DOI: 10.1021/la0342316
|View full text |Cite
|
Sign up to set email alerts
|

Heat Capacity Study to Evidence the Interactions between Cyclodextrin and Surfactant in the Monomeric and Micellized States

Abstract: The heat capacities of transfer (∆Cpt) of hydroxypropyl-R-cyclodextrin and hydroxypropyl-γ-cyclodextrin (0.05 mol kg -1 ) from water to aqueous solutions of sodium hexanoate, sodium decanoate, and sodium dodecanoate were determined at 298 K. The measurements were extended to both the pre-and the postmicellar regions. The shape of the ∆Cp t as a function of the surfactant concentration curve is system specific. As well, the ∆Cpt magnitude depends on the macrocycle cavity being largely negative for HP-γ-CD. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
(127 reference statements)
1
17
0
Order By: Relevance
“…However, Milioto et al. clearly demonstrated that HP‐α‐CD or HP‐γ‐CD interacted with sodium alkanoates‐based micelles 41,42,43. In that case, CDs adsorbed on the micelle surface because of hydrogen bonding between the carboxylate groups of the micelle components and the CD hydroxyle functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, Milioto et al. clearly demonstrated that HP‐α‐CD or HP‐γ‐CD interacted with sodium alkanoates‐based micelles 41,42,43. In that case, CDs adsorbed on the micelle surface because of hydrogen bonding between the carboxylate groups of the micelle components and the CD hydroxyle functions.…”
Section: Introductionmentioning
confidence: 99%
“…The binding constant and the change in the property for the host-guest complex formation can be simultaneously estimated from the bulk thermodynamic properties like calorimetry (Castronuovo, Elia, Niccoli, & Velleca, 2003), density (Martínez et al, 1999) and heat capacity (De Lisi, Lazzara, Milioto, Muratore, & Terekhova, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent results from the study of the enthalpy of transfer of CD from water to aqueous surfactant solutions suggest the existence of interactions between micelles and CDs in systems using hydrogenated [43,44] and fluorinated [45] alkanoates. Quantitative analysis of the postmicellar region indicates that the CD -micelle forces are ion -dipole (carboxylate head=hydroxylic group) in nature.…”
Section: Introductionmentioning
confidence: 99%